Assessment Of Pit And Fissure Sealants Following Enamel Deproteinization Using Three Different Methods For Shear Bond Strength And Microleakage- A Comparative In Vitro Study (Journal of Pharmaceutical Negative Results, 2022)
Background: Occlusal caries is thought to be most effectively prevented by sealing pits and fissures. The deproteinization may have an impact on the adhesiveness and retentive ability of pit and fissure sealant, among other factors.Aim: To assess the impact of three deproteinizing agents applied before and after acid etching on the microleakage and shear bond strength of pit and fissure sealants.Methodology: Included were one hundred fifty-four extracted, healthy human maxillary and mandibular molars. 6.25% sodium hypochlorite (NaOCl), 10% papain gel, and 6% bromelain gel were the deproteinizing agents that were used. Group A (deproteinization done after etchant application), Group B (deproteinization done before etching), and Group C (control group) were the three groups into which the samples were split. Based on the type of deproteinization agent used, Group A and Group B were further divided into three groups. After that, sealant (3M ESPE Clinpro) was applied and given a 20-second light cure. Using a stereomicroscope magnified 40 times to evaluate microleakage and a universal testing machine to measure shear bond strength (SBS), respectively.Results: For microleakage, scores were lowest for Bromelain group, followed by Papain group and NaOCl group and highest for control group. Statistically significant difference was found between control and bromelain group (P=0.039). Mean values for shear bond strength was highest for Bromelain group (18.65±3.56), followed by Papain group (12.00±2.46), NaOCl group (9.77±2.31) and control group (7.71±1.58). Statistically significant differences were found for Papain group (P=0.047) and Bromelain group (P=0.047). Also, deproteinization before acid etching showed superior results both for SBS and microleakage.Conclusion: When deproteinization is performed before acid etching, the SBS values increase and the sealant microleakage score decreases. As an alternative to 5.25% sodium hypochlorite, 10% papain enzyme and 6% bromelain enzyme can be used successfully. The bromelain group, however, demonstrated superior results because it effectively removed the organic materials from tooth surface.